Heritable and inducible gene knockdown in astrocytes or neurons in vivo by a combined lentiviral and RNAi approach - Heitz, Fabrice; Johansson, Torbjörn; Baumgärtel, Karsten; Gecaj, Rreze; Pelczar, Pawel; Mansuy, Isabelle M. (Frontiers in Cellular Neuroscience, 2014)
Gene knockout by homologous recombination is a popular method to study gene functions in the mouse in vivo. However, its lack of temporal control has limited the interpretation of knockout studies because the complete elimination of a gene product often alters developmental processes, and can induce severe malformations or lethality. Conditional gene knockdown has emerged as a compelling alternative to gene knockout, an approach well established in vitro but that remains challenging in vivo, especially in the adult brain. Here, we report a method for conditional and cell-specific gene knockdown in the mouse brain in vivo that combines Cre-mediated RNA interference (RNAi) with classical and lentivirus-mediated transgenesis. The method is based on the inducible expression of a silencing short hairpin RNA (shRNA) introduced in mice by lentivirus-mediated transgenesis, and on its activation by excision of a floxed stop EGFP reporter with an inducible Cre recombinase expressed in astrocytes or in neurons. This dual system should be of broad utility for comparative studies of gene functions in these two cell types in vivo.